A case study on the structural assessment of fire damaged building - Osman, M.; Sarbini, N.; Ibrahim, I.; Ma, C.; Ismail, Mohamed; Mohd, M. (2017)
© Published under licence by IOP Publishing Ltd. This paper presents a case study on the structural assessment of building damaged by fire and discussed on the site investigations and test results prior to determine the existing condition of the building. The building was on fire for about one hour before it was extinguished. In order to ascertain the integrity of the building, a visual inspection was conducted for all elements (truss, beam, column and wall), followed by non-destructive, load and material tests. The load test was conducted to determine the ability of truss to resist service load, while the material test to determine the residual strength of the material. At the end of the investigation, a structural analysis was carried out to determine the new factor of safety by considering the residual strength. The highlighted was on the truss element due to steel behaviour that is hardly been predicted. Meanwhile, reinforced concrete elements (beam, column and wall) were found externally affected and caused its strength to be considered as sufficient for further used of building. The new factor of safety is equal to 2, considered as the minimum calculated value for the truss member. Therefore, this fire damaged building was found safe and can be used for further application.